Engine noise: An overview on current research trends - Hanouf, Zahir; Mohd. Nor, Mohd. Jailani; Faris, Waleed Fekry (Fakulti Kejuruteraan, Universiti Kebangsaan Malaysia, 2007)
Engine noise is one of the most researched subjects in the past few years, with the new international regulations on noise levels and doses, automotive industries are coming under much scrutiny. Many sources of noise related to automotives are identified but the main one remains to be the engine. In this paper, we classify different types of noises related to the engine and explain the reasons behind them and how to detect them as well. Also, the paper will review the main research works related to the subject and critically review them about measuring techniques and noise detection methodologies currently used. This paper is intended to be an overview on the current research trends on this subject to help the researchers in this field to align and plan their future research activities.